Correction: In situ electrochemical H2 production for efficient and stable power-to-gas electromethanogenesis. Issue 15 (8th July 2021) - Kracke, Frauke; Deutzmann, Jörg S.; Gu, Wenyu; Spormann, Alfred M.
Abstract : Correction for ' In situ electrochemical H2 production for efficient and stable power-to-gas electromethanogenesis' by Frauke Kracke et al., Green Chem., 2020, 22, 6194–6203, DOI: ; 10.1039/D0GC01894E .